Identifying yeasts using surface enhanced Raman spectroscopy - Lemma, Tibebe [UNESP]; Wang, Jin; Arstila, Kai; Hytönen, Vesa P.; Toppari, J. Jussi (Elsevier, 2019)
The molecular fingerprints of yeasts Saccharomyces cerevisiae, Dekkera bruxellensis, and Wickerhamomyces anomalus (former name Pichia anomala) have been examined using surface-enhanced Raman spectroscopy (SERS) and helium ion microscopy (HIM). The SERS spectra obtained from cell cultures (lysate and non-treated cells) distinguish between these very closely related fungal species. Highly SERS active silver nano-particles suitable for detecting complex biomolecules were fabricated using a simple synthesis route. The yeast samples mixed with aggregated Ag nanoparticles yielded highly enhanced and reproducible Raman signal owing to the high density of the hot spots at the junctions of two or more Ag nanoparticles and enabled to differentiate the three species based on their unique features (spectral fingerprint). We also collected SERS spectra of the three yeast species in beer medium to demonstrate the potential of the method for industrial application. These findings demonstrate the great potential of SERS for detection and identification of fungi species based on the biochemical compositions, even in a chemically complex sample.
Keywords: Aggregate; Helium ion microscopy; SERS; Silver nanoparticle; Yeast